An Experimental Lymphoscintigraphy Study in an Acute Unilateral Deep Venous Thrombosis Model - Koc, Zehra Pinar; Burma, Oktay; Uysal, Ayhan; Mitil, Huseyin Aydin (Mary Ann Liebert Inc, 2013)
Background: The aim of this study is to investigate the effect of both inguinal exploration and deep venous thrombosis on lymphatic flow in an experimental model of unilateral acute obstruction of the femoral vein. Methods and Results: Eighteen male New Zealand White rabbits were the subjects of this study. The rabbits were divided into three groups; Group 1 (n = 6, control), Group 2 (n = 6, sham), and Group 3 (n = 6, operation). After the lymphoscintigraphy was performed on the Group 1 animals, the rabbits in Group 2 and Group 3 underwent intervention. In Group 3, the femoral vein was clipped and excised. In Group 2, an inguinal incision was performed and the clip materials were placed beneath the femoral vein. After the surgical intervention, lower extremity lymphoscintigraphy by subcutaneous administration of Tc-99m nanocolloid was performed in dynamic and static manner in Groups 2 and 3 on the second, fifteenth and thirtieth days after the operation. Unilateral impairment of the lymphatic flow in the operated extremity was observed in Group 3 in the early and late postoperative period but unilateral lymphatic impairment was observed in Group 2 in only the late postoperative period. Conclusion: The lymphatic impairment in an operated extremity might be the consequence of surgical intervention rather than acute venous obstruction in cases where both situations are observed.
Keywords: Lymph-Drainage; Cancer; Edema